Numerical investigation for the influence of suspended sediment on salinity distribution in the Qiantang Estuary, China - Rong, Zheng; Chunhong, Hu; Zhilin, Sun; Yizhi, Sun (Frontiers in Marine Science, 2024)
Numerous studies have demonstrated that high suspended sediment concentration (SSC) can change density distribution and affect water mixing, but few scholars have investigated this impact on numerical simulations of estuarian salinity distribution. The Qiantang Estuary is a macro-tidal estuary with high SSC, which has a more significant influence on water density than that of salinity. Therefore, this paper established a three-dimensional (3D) numerical model coupling flow, salinity and SSC based on Delft3D and first analyzes the impact of SSC on salinity distribution under different runoff and tidal conditions in the Qiantang Estuary. The results indicated that simulated salinity generally decreases when considering the impact of SSC, suggesting a weakening effect on saltwater intrusion. The distribution of salinity difference (ΔS) and SSC show a strong spatial and temporal correlation, and ΔS peak increases and shifts upstream as the tidal range increases or runoff discharge decreases. The mechanism of SSC influencing saltwater intrusion can be summarized as follows: On the one hand, SSC increases the water density, which weakens the driving force for saltwater to move upstream, causing a decrease in flood current velocity and water level, and thereby diminishing the advective transport of salinity. On the other hand, SSC enhances density stratification, which weakens vertical turbulence and reduces the dispersive transport of salinity. These combined effects reduce both the advective and diffusive salinity fluxes during the flood tide, ultimately leading to a decrease in upstream salinity. Therefore, neglecting this effect in estuaries with high SSC can cause significant deviations in salinity simulation results, especially under low-flow and high-tide conditions.